2017
DOI: 10.1128/jcm.02284-16
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin as a Biomarker for Melioidosis Disease Progression and Management

Abstract: Melioidosis is a neglected tropical disease that is caused by the bacterium Burkholderia pseudomallei and is underreported in many countries where the disease is endemic. A long and costly administration of antibiotics is needed to clear infections, and there is an unmet need for biomarkers to guide antibiotic treatment and increase the number of patients that complete therapy. We identified calprotectin as a lead biomarker of B. pseudomallei infections and examined correlations between this serum protein and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Patient enrolment and clinical characteristics of the study population included here were partly reported elsewhere [ 28 ]. Clinical samples were collected over a period of 2 years (2013–2015).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Patient enrolment and clinical characteristics of the study population included here were partly reported elsewhere [ 28 ]. Clinical samples were collected over a period of 2 years (2013–2015).…”
Section: Resultsmentioning
confidence: 99%
“…Melioidosis patients older than 18 years were enrolled in this study as described elsewhere [ 28 ] . Clinical samples, matched PBMCs and sera were collected over a period of 2 years (2013–2015) from acute and confirmed cases of melioidosis during the antibiotic treatment phase.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations